Are "Well-Told" Stories of Cancer Worn Out? Insights on Persuasion Characteristics Used in Cancer Narrative PSAs. Issue 3 (1st September 2020) - Rodgers, Shelly; Stemmle, Jon
Abstract: There has been limited attention to cancer narrative public service announcements (CNPSAs) despite their potential to educate and engage consumers. Attributes of "well-told" stories are assumed to lead to narrative success, yet seldom do studies describe the nature of characteristics used in real-world advertisements. A major goal of the research was to quantitatively examine the more qualitative aspects of narratives by describing persuasion characteristics present in CNPSAs for two of the most common cancers in women (breast) and men (prostate). This was accomplished with a content analysis of 402 breast and prostate CNPSAs. Descriptive results were linked to behavioral engagement to draw conclusions that hold important implications to explain the role of narrative advertising as a social force. Analyses provide support for the central hypothesis of the study, indicating that effective cancer narratives are at least in part a product of the content, form, and context features of CNPSAs. This research is intended to inform researchers and practitioners in narrative approaches used to influence cancer prevention and control behaviors, as well as indicating which narrative approaches might be better suited for engaging individuals affected by cancer.